Trends in e-visit adoption among U.S. office-based physicians: Evidence from the 2011–2015 NAMCS. (September 2019) - Hong, Young-Rock; Turner, Kea; Yadav, Sandhya; Huo, Jinhai; Mainous, Arch G.
Abstract: Background: Electronic visits (e-visits) have the potential to expand patients' access to care and reduce healthcare costs. We aimed to describe trends in e-visit adoption among the U.S. office-based physicians and examine physician-and practice-level factors associated with e-visit adoption. Methods: This was a retrospective observational study of 2011–2015 National Ambulatory Medical Care Survey. We used the Cochran-Armitage tests to evaluate trend changes in e-visit adoption among the U.S. office-based physicians. Multivariable logistic regression was used to calculate the odds of adopting e-visits adjusting for physician and practice characteristics. Results: Our sample included 10, 767 respondents, representing 327, 836 office-based physicians in the U.S. Our analysis indicated that, in 2015, 15.9% of physicians adopted e-visits, which is a minor increase of 2.2% in total utilization of 13.7% in 2011. The likelihood of adopting e-visits was 2.7 times higher for physicians who have fully implemented electronic health records systems compared (odds ratio, 2.66, [95% CI, 2.16–3.28]) to physicians who have not implemented EHRs. Other predictors of e-visit adoption included primary care rather than specialty care, capitated payment model, and having a secure messaging capability. Conclusions: Our study demonstrates that overall e-visit adoption is low and has not been implemented as rapidly as other health information technologies. While use of secure information technology could be a facilitator for e-visit implementation, there are other barriers affecting widespread adoption. E-visits are a promising strategy for increasing patients' access to care. Future research is needed to explore implementation barriers that might be impeding e-visit adoption.